Mulheres no cinema de Alagoas : Mostra Sururu de Cinema Alagoano (2009 - 2018) - Silva, Maysa Santos da (2020)
This dissertation investigates the cinema made by female directors in the state of Alagoas, with nine editions of the Mostra Sururu de Cinema Alagoano (2009-2018). The research was divided into four stages: the first part reflects on the identity of the Northeast, the cinematographic production of the Region and the female presence, also highlighting the contemporary production of Northeasterners and Northeasterners; the second part deals with the historical trajectory of cinema in Alagoas, its main aspects of development and achievements for the cultural sector. The third part of the work describes the editions of Mostra Sururu, highlighting the participation of Alagoas directors. In the fourth and last stage, from the perception of directors who were highlighted in the editions of Mostra Sururu, the research discusses how their narratives reflect gender issues in cinema, the political, economic and social determinations that mark their trajectories, also reflecting the contexts in which the films are inserted and also the Alagoas production of female authorship in cinema.